Strengthening Children’s Faith Through SEKAMI Activities at St. Joseph Watulajar Parish: The Effectiveness of SEKAMI Activities in Strengthening Children’s Faith at St. Joseph Watulajar Parish (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity was conducted to address the low level of children’s participation and engagement in church-based faith development programs at St. Yoseph Watulajar Station. The activity aimed to analyze the effectiveness of SEKAMI (Pontifical Missionary Childhood Association) activities in strengthening children’s faith. A qualitative descriptive approach was employed, involving direct observation, interviews with facilitators and participants, and documentation. The collected data were analyzed using a SWOT framework to identify strengths, weaknesses, opportunities, and challenges in the implementation process. The results showed that well-designed, creative, and participatory SEKAMI activities showed clear improvement in children’s involvement, enthusiasm, and confidence in engaging with faith-related practices such as prayer, group interaction, and religious reflection. Children showed more regular attendance, more active participation in prayer, and a stronger sense of belonging to the Church. They also demonstrated more positive attitudes toward church participation, including greater consistency in attending spiritual activities. In addition, the program strengthened social relationships among participants and encouraged a sense of responsibility within the group. These findings indicate that SEKAMI activities are effective in strengthening children’s faith through meaningful and participatory experiences. In conclusion, SEKAMI activities provide an effective, contextual, and sustainable model of faith formation that is responsive to the challenges faced by children in the modern era.